Generalised joint hypermobility increases ACL injury risk and is associated with inferior outcome after ACL reconstruction: a systematic review. Issue 1 (10th November 2019) - Sundemo, David; Hamrin Senorski, Eric; Karlsson, Louise; Horvath, Alexandra; Juul-Kristensen, Birgit; Karlsson, Jon; Ayeni, Olufemi R; Samuelsson, Kristian
Abstract : Objectives: To investigate the association between generalised joint hypermobility (GJH) and ACL injury risk. Secondary aims involved evaluating associations between GJH and postoperative outcome (including graft-failure risk, knee laxity and patient-reported outcome). Furthermore, we aimed to compare the performance of different grafts in patients with GJH. Methods: Databases MEDLINE/PubMed, EMBASE and the Cochrane Library were searched, including 2760 studies. Two reviewers independently screened studies for eligibility. A modified version of the MINORS score was applied for quality appraisal. Studies assessing GJH while reporting the risk of ACL injury and/or postoperative outcome were included. Results: Twenty studies were included, using several different methods to determine GJH. There was consistent evidence showing that GJH is a risk factor for unilateral ACL injury in males, while in females, the results were conflicting. There was limited evidence associating GJH with increased knee laxity 5 years postoperatively. There was consistent evidence of inferior postoperative patient-reported outcome in patients with GJH. Moreover, there was limited yet consistent evidence indicating that patellar-tendon autografts are superior to hamstring-tendon autografts in patients with GJH in terms of knee laxity and patient-reported outcome. There was insufficient evidence to draw conclusions regarding the outcomes of bilateral ACL injury and graft failure. Conclusions: In men, GJH was associated with an increased risk of unilateral ACL injury. Moreover, GJH was associated with greater postoperative knee laxity and inferior patient-reported outcome. Based on the available evidence, a patellar-tendon autograft appears to be superior to a hamstring-tendon autograft in patients with GJH. However, the included studies were heterogeneous and there is a need for consensus in the assessment of GJH within sports medicine.